An existence theorem for optimal control with nonstandard cost functionals - R. N. Mukherjee; Shiv Prasad (International Journal of Mathematics and Mathematical Sciences)
An existence theorem for optimal control is obtained for a general nonstandard cost functional of fractional type in this work. As an application of our result we can derive an existence theorem for optimal control given by M. B. Subrahamanyam for a cost functional, which is a ratio of two given integral cost functionals.